2012
DOI: 10.1042/bsr20120113
|View full text |Cite
|
Sign up to set email alerts
|

Cry1Aa binding to the cadherin receptor does not require conserved amino acid sequences in the domain II loops

Abstract: Characterizing the binding mechanism of Bt (Bacillus thuringiensis) Cry toxin to the cadherin receptor is indispensable to understanding the specific insecticidal activity of this toxin. To this end, we constructed 30 loop mutants by randomly inserting four serial amino acids covering all four receptor binding loops (loops α8, 1, 2 and 3) and analysed their binding affinities for Bombyx mori cadherin receptors via Biacore. High binding affinities were confirmed for all 30 mutants containing loop sequences that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…This conclusion also agrees with the previously reported hypothesis that Cry1Aa binds to cadherin‐like receptors at multiple sites presented by several loops (Fujii et al. ). The current study demonstrates that loop 2 is one of the most effective regions for introducing Cry1Aa affinity maturation to cadherin‐like receptors for the purpose of directed evolution of the toxin.…”
Section: Discussionsupporting
confidence: 93%
“…This conclusion also agrees with the previously reported hypothesis that Cry1Aa binds to cadherin‐like receptors at multiple sites presented by several loops (Fujii et al. ). The current study demonstrates that loop 2 is one of the most effective regions for introducing Cry1Aa affinity maturation to cadherin‐like receptors for the purpose of directed evolution of the toxin.…”
Section: Discussionsupporting
confidence: 93%
“…Mutant libraries have been constructed in specific areas of the 3D-Cry toxin using several molecular approaches such as degenerated primers [ 133 , 134 , 135 ], DNA shuffling [ 136 , 137 ], or using a previously constructed antibodies library [ 138 ]. All these libraries were screened for variants showing high binding affinity toward two of the most well-known receptors (cadherin like receptor and APN), and although an increase of binding affinity is not a guarantee for increased toxicity [ 134 , 135 ], some authors have managed to obtain enhanced 3D-Cry toxin variants compared to the parental toxin.…”
Section: “In Vitro Evolution” Of 3d-cry Toxins: An Historical Persmentioning
confidence: 99%
“…These changes may suggest a variation in mutant toxicity, as in the study conducted by Fuji et al that highlights the importance of the α8 loop of the Cry1Ab toxin in the interactions of the toxin with the cadherin BT-R1 receptor. 30,31 This suggests that mutants may be potentiated concerning the binding to the receptor or, in another context, an improvement in additional interactions with target insects that have not been reported yet.…”
Section: Structural Analysis Of the Best Sequences Obtained Using Hiddenmentioning
confidence: 97%
“…Several studies state that loop 3 region of Cry toxins is directly related to the significant binding to cadherin BT-R1 receptors with Cry1Aa and Cry1Ab binding to the BtR receptors of Heliothis virescens. 30 Studies on mutagenesis in coding regions to loop 3 conducted by Pacheco et al 34 demonstrate the importance of this amino acid region, in which variations of toxicity could be correlated to changes made in Cry1Ab loop 3, ascribing that the lack of binding of toxins to the BBMV of M. sexta result in changes in oligomerization and affect the toxicity of the protein Almost all mutants show changes in domain III, except for S15pop1-1. Studies conducted by Burton et al reported reductions in the toxicity of Cry1Ac proteins when making changes in domain III through mutagenesis.…”
Section: Structural Analysis Of the Best Sequences Obtained Using Hiddenmentioning
confidence: 99%